An Observational Study on Domestic Violence, Marital Satisfaction, and Psychiatric Morbidities in Wives of Alcohol Use Disorder Males - Roshani K Patel; Pradip N Dalsaniya; Punit Patel; Mukesh K Patel (Indian Journal of Private Psychiatry)
Background: Alcohol is a commonly consumed substance that induces intoxication and can lead to dependence. Alcoholism is often referred to as a family disease due to its harmful impact on the lives of family members and its maximum impact is felt on spouses. Understanding the pivotal role spouses plays in alcohol treatment, there is thus a need to study domestic violence, marital satisfaction, and psychiatric morbidity in spouses of alcohol-dependent patients to understand and address such issues. Aims: This study aimed to assess domestic violence, marital satisfaction, and psychiatric morbidity in spouses of men with alcohol dependence syndrome and explore the association. Materials and methods: A total of 105 spouses of men with alcohol dependence syndrome were evaluated. Severity of alcohol dependence was assessed using severity of alcohol dependence questionnaire (SADQ), marital satisfaction in spouses was assessed using the MAT, domestic violence was assessed using domestic violence questionnaire, mini-international neuropsychiatric interview (MINI) was used to screen for the possible presence of psychiatric morbidity among spouses. Depression and anxiety severity was assessed using Hamilton Rating Scale for Depression (HAM-D) and Hamilton Anxiety Rating Scale (HAM-A). Results: Out of 105 cases, we found that the mean age of spouse was 22.29. Majority of patients had severe alcohol dependence (46.7%) based on SADQ score. Severe level of domestic violence was present in (28.6%) of spouses. Most of the spouses (50.5%) had a lower level of marital satisfaction and (82.86%) spouses had a psychiatric disorder. Primarily depression and anxiety disorder were present. Domestic violence, marital dissatisfaction, and severity of depression and anxiety in spouses were significantly associated with alcohol dependence. Conclusion: Spouses of alcoholic husbands suffer from high levels of domestic violence, with marital satisfaction being low and psychiatric morbidity in spouses of alcohol-dependent men are high. Addressing these issues will be beneficial as spouses are known to play an important role in the treatment of alcohol dependence syndrome.